PELAJARAN PENTING DALAM MASA PEMERINTAHAN ORDE BARU - Leonard Tasuno Laiya (Fakultas Hukum Universitas Tarumanagara, 2021)
Dur ng the New Order era he (often abbrev ated as New Order) was the term for the re gn of Pres dent Soeharto n ndones a. The New Order was founded by the Old Order, wh ch refers to the era of Soekarno's government. As we know, th s new order era occurred after the destruct on of the old order and before the format on of the reform order unt l now The b rth of the New Order began w th the ssuance of an Order on March 11, 1966. The New Order lasted from 1966 to 1998. At that t me he appo nted Sukarno as the f rst Pres dent of the Republ c of ndones a. The transfer of off ce occurred n 1966, w th the replacement of the old order wh ch referred to the era of Pres dent Soekarno's adm n strat on. Wh ch has stepped down s nce the G30S PK nc dent emerged. n th s art cle, we w ll d scuss the h story of the old order from the beg nn ng of ts format on to the format on of the next per od, namely the new order. n th s art cle we w ll also d scuss the h story of the new order and other mportant events, and w ll also d scuss the h story of the reformat on era, namely the per od when the new order was destroyed and replaced by a new per od, namely the reform era that has been n effect unt l now